2008
DOI: 10.1074/jbc.m805822200
|View full text |Cite
|
Sign up to set email alerts
|

RalA Functions as an Indispensable Signal Mediator for the Nutrient-sensing System

Abstract: Cells sense nutrients present in the extracellular environment and modulate the activities of intracellular signaling systems in response to nutrient availability. This study demonstrates that RalA and its activator RalGDS participate in nutrient sensing and are indispensable for activation of mammalian target of rapamycin complex 1 (mTORC1) induced by extracellular nutrients. Knockdown of RalA or RalGDS abolished amino acidand glucose-induced mTORC1 activation, as judged by phosphorylation of S6 kinase and eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 46 publications
1
56
0
Order By: Relevance
“…We and others (31) observed that recombinant FKBP38 inhibited mTORC1 signaling in cells only when it was highly overexpressed, which may explain the absence of the effect of FKBP38 in similar experiments performed by some groups (33,34). The requirement of high levels of recombinant FKBP38 to FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others (31) observed that recombinant FKBP38 inhibited mTORC1 signaling in cells only when it was highly overexpressed, which may explain the absence of the effect of FKBP38 in similar experiments performed by some groups (33,34). The requirement of high levels of recombinant FKBP38 to FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…Because FKBP38 binds mTOR through a region that overlaps with the PA-binding FRB domain (13,14), it appeared plausible that PA could compete with FKBP38 for mTOR binding as a mechanism of activating mTORC1. However, although several groups independently demonstrated a role of FKBP38 as a negative regulator of mTORC1 (13,31,32), others challenged this conclusion (33,34). Therefore, we deemed it necessary to reexamine the role of FKBP38 in mTORC1 signaling in the Chen laboratory.…”
Section: Pa Stimulates Mtorc1mentioning
confidence: 99%
“…23 The larger FKBP38 has been proposed to be an endogenous inhibitor of mTOR by binding to mTOR independently of rapamycin in a manner displaceable by the mTOR activator Rheb. [24][25][26][27] However, the biochemical interaction of FKBP38 with Rheb or mTOR as well as its role in the cellular regulation of mTOR could not be replicated by several other groups, [28][29][30][31] and the role of FKBP38 in mTOR regulation remains controversial.…”
Section: The Role Of Fkbps In Intracellular Signalingmentioning
confidence: 99%
“…Several GTPases (e.g. RAGs and RalA) have also been shown to promote mTORC1 signaling in response to amino acid sufficiency (61)(62)(63). A recent model posits that GTP-loaded RAG heterodimers bind raptor and induce the recruitment of mTORC1 from an ill defined cytoplasmic compartment to a Rab7-positive late endosomal membrane compartment that contains the mTORC1 activator Rheb (62).…”
Section: Regulation Of Mtorc Signaling Networkmentioning
confidence: 99%